2015
DOI: 10.1016/bs.pmbts.2015.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G Protein Signaling 2

Abstract: Regulators of G protein signaling (RGS) proteins of the B/R4 family are widely expressed in the cardiovascular system where their role in fine tuning G protein signaling is critical to maintaining homeostasis. Among members of this family, RGS2 and RGS5 have been shown to play key roles in cardiac and smooth muscle function by tightly regulating signaling pathways that are activated through Gq/11 and Gi/o classes of heterotrimeric G proteins. This chapter reviews accumulating evidence supporting a key role for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 79 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…Our findings are consistent with a previous report showing that ANP and a cGMP analogue hyperpolarized cultured mesangial cells and that this hyperpolarization was inhibited by potassium channel blocker. 34 Recently, Osei-Owusu et al 25,27 demonstrated that endothelial-specific deletion of Rgs2 markedly inhibits EDHF-dependent relaxation of mouse mesenteric arteries. We found that ANP significantly increased Rgs2 mRNA expression levels in HUVECs and that ANPmediated hyperpolarization of HUVECs was abolished under Rgs2 siRNA transfection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings are consistent with a previous report showing that ANP and a cGMP analogue hyperpolarized cultured mesangial cells and that this hyperpolarization was inhibited by potassium channel blocker. 34 Recently, Osei-Owusu et al 25,27 demonstrated that endothelial-specific deletion of Rgs2 markedly inhibits EDHF-dependent relaxation of mouse mesenteric arteries. We found that ANP significantly increased Rgs2 mRNA expression levels in HUVECs and that ANPmediated hyperpolarization of HUVECs was abolished under Rgs2 siRNA transfection.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Osei-Owusu et al 25,27 demonstrated that endothelial-specific deletion of Rgs2 markedly inhibits EDHF-dependent relaxation of mouse mesenteric arteries. We found that ANP significantly increased Rgs2 mRNA expression levels in HUVECs and that ANP-mediated hyperpolarization of HUVECs was abolished under Rgs2 siRNA transfection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RGS1 functions to regulate B lymphocyte maturation induced by chemokines and can also be found in T lymphocytes, natural killer (NK) cells, dendritic cells, and monocytes (4,38,94,113,169). The next RGS protein, Rgs2, is ubiquitously expressed, with expression documented in the CNS, heart, vasculature, kidney, immune system, lungs, bone and ovaries (13,89,98,125,163). The main function of RGS2 is to regulate G ␣q and G ␣i signaling (64,89,92,180).…”
Section: The B/r4 Family Of Rgs Proteinsmentioning
confidence: 99%
“…Expression of RGS2 is inversely related to blood pressure (BP), as subjects with hypotension (ie, Bartter’s or Gitelman’s syndromes) exhibit increased RGS2 but those with hypertension exhibit reduced RGS2 levels. 7 Rodent models support a critical role for RGS2 in the function of the vasculature, 8–11 control of blood pressure, 12 and the development and function of adipose 13 and placenta. 14…”
mentioning
confidence: 99%